Study of Risk factors of Coronary Heart Disease in Urban Slums of Patna - Singh, Rashmi; Mukherjee, Madhumita; Kumar, Rajeev; Singh, Ritu; Pal, Ranabir (Nepal Journal of Epidemiology, 2012)
Background Coronary Heart Diseases (CHDs) are imminent cause of disability and death with economic adverse effects in the disadvantaged population in India. Materials and Methods This population based study was conducted from 1st December 2010 till 31st May 2011 among the adults in the slums of Patna to assess the magnitude and risk factors of CHDs concerning age, sex, tobacco use, alcohol consumption, physical activity, weight, height, waist circumference, blood pressure and random capillary blood glucose (RCBG). Results Among 3118 participants 16.36 percent (males 18.79 %, females 14.48 %) were hypertensive; 26.3 percent (males 25.94 %, females 26.58 %) had elevated RCBG; 4.46 percent were Diabetic. High body mass index (BMI), waist circumference (WC) and waist to height ratio (WHtR) was noted in 31.94 percent (males 31.83%, females 32.03%), 50.45 percent (males 39.1%, females 59.17%), 86.53 percent (male 83.12%, female 89.15%) respectively; tobacco users were 12.54 percent, while 9.14 percent reported alcohol consumption; 33.64 percent were sedentary (males 30.55%, females 37.65%). BMI, WC, WHtR, tobacco use, alcohol consumption and physical inactivity were significantly associated with hypertension (p < 0.05). Elevated RCBG was significantly associated with increased BMI, WC, WHtR. Multivariate logistic regression revealed that BMI, WHtR and alcohol were associated with hypertension, not with elevated RCBG. Conclusion Our study indicated that CHDs and their risk factors are not only limited to affluent societies but also affect the underprivileged mass. Preventive care and multipronged intervention including extensive behavior change communication needs to be organized to reduce the risk of CHDs in urban poor. DOI: http://dx.doi.org/10.3126/nje.v2i3.6902 Nepal Journal of Epidemiology 2012;2(3): 205-12